Revealing Politeness Through Illocutionary Act Approach in World Health Organization Staff’s Responses at Corona Virus Press Briefing - Farah Larissa Aryanti; Lina Purwaning Hartanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study revealed politeness through illocutionary acts theory in a corona virus press briefing held by WHO (World Health Organization). Taken from a video press briefing entitled  “Live from WHO Headquarters - COVID-19 daily press briefing on March 20th,  2020” uploaded in World Health Organization YouTube Channel, this study were (1) discovering how the illocutionary act and indirect speech act by Yule (1996) represented then (2) linked to the politeness and the universality of indirect speech acts by Brown, et. Al. (1987). The method used qualitative descriptive. This study contributed (1) theoretically to provide a sample of politeness through illocutionary act  and indirect speech act taken from a situation in press briefing and (2) practically to give an example of politeness that could be a reference of polite communication when a speaker utters and hopes an action were done by the hearer. The results were (1) politeness in communication could avoid conflict by using indirect speech acts; (2) using generalization and giving resolution without abusing at a certain situation could give politeness in utterances.